Curcumin's Ability to Treat Polycystic Ovary Syndrome (PCOS) in Women - Aya Hassan Ali Shadhan; Nasreen Hussein Ali Mohammed; Noor Mohammed Masoud Sami kamel; Alaq Saadallah Abdulhamid Amin (American Journal of Biology and Natural Sciences, 2025)
Polycystic ovary syndrome is known as a hormonal disorder that is common among women at a rate of 20% and occurs when the ovaries produce a high percentage of androgens, which include male sex hormones that are naturally present in women in very small amounts and proportions. Important features of this disease include oxidative stress, inflammation, hyperglycemia, hyperlipidemia, androgenism, and insulin resistance. Metformin, eflornithine, and oral contraceptives are widely used for treatment, not to mention the many side effects, so in this study we talk about something that may have potential in reducing inflammation and curing it permanently. Curcumin is a natural, non-inert polyphenolic compound extracted from turmeric. It has anti-inflammatory and antibacterial activities. It lowers blood sugar levels in a variety of conditions. The research also provides suggestions for developing appropriate drugs against PCOS from curcumin.